Acid blue 29 decolorization and mineralization by anodic oxidation with a cold gas spray synthesized Sn–Cu–Sb alloy anode. (April 2016) - do Vale-Júnior, Edilson; Dosta, Sergi; Cano, Irene Garcia; Guilemany, Josep Maria; Garcia-Segura, Sergi; Martínez-Huitle, Carlos Alberto
Abstract: The elevated cost of anodic materials used in the anodic oxidation for water treatment of effluents undermines the real application of these technologies. The study of novel alternative materials more affordable is required. In this work, we report the application of Sn–Cu–Sb alloys as cheap anodic material to decolorize azo dye Acid Blue 29 solutions. These anodes have been synthesized by cold gas spray technologies. Almost complete decolorization and COD abatement were attained after 300 and 600 min of electrochemical treatment, respectively. The influence of several variables such as supporting electrolyte, pH, current density and initial pollutant concentration has been investigated. Furthermore, the release and evolution of by-products was followed by HPLC to better understand the oxidative power of Sn–Cu–Sb electrodes. Highlights: Stable and reproducible Sn–Cu–Sb anodes were synthesized by cold gas spray. Almost complete decolorization is achieved by anodic oxidation in sulfate media. Total COD abatement at low current densities of 10 mA cm -2 with Sn–Cu–Sb anodes. Pollutant heteroatoms released mainly as sulfate, nitrate and ammonium.